Isolasi dan Pengukuran Aktivitas Enzim Bromelin dari Ekstrak Kasar Batang Nanas (Ananas comosus) Berdasarkan Variasi pH - N, Nurhidayah; M, Masriany; Masri, Mashuri (Jurusan Biologi UIN Alauddin Makassar, 2013)
This research aims to determine the highest protein content and the optimum activity of the enzyme bromelain extracted from pineapple stem. This research was conducted at the Laboratory of Microbiology Makassar Alauddin State Islamic University in May 2013. Variable in this study was the isolation and measurement of bromelain enzyme activity as the independent variable while the crude extract of pineapple stem by variations in pH as the dependent variable. The type of this research was experiments with bradford method for determination of protein content enzyme bromelain, with ammonium sulfate concentration variation for precipitation was 10-60%, as well asthe determination of the enzyme bromelain activity at variation pH was 4.0; 5.0, 6.0; 7.0 and 8.0, at 650C temperature with incubation time was 10 minutes. Each stage has done three times in repetition and analyzed spectrometry. The results showed the highest levels of protein precipitation with ammonium sulfate at 60% was 37,785 mg/ml. While the optimum pH of the enzyme bromelain activity at pH 6.0 was 1.021 activity units /gram.Keywords: bromelain enzyme, Pineapple stem (Ananas comosus), precipitation with ammonium sulfate, protein contents, pH